The Effect of Word Meaning Deriving Strategy Instruction: The Case of EFL Students in Taiwan - Chin Min Lin (TEFLIN, 2008)
This study intends to find out the effect of teaching word meaning deriving strategies to EFL Students in Taiwan. The subjects were one class of the first year students attending a junior college in Taiwan. They were given a pre-test, which contained a passage, 10 vocabulary test items and 10 strategy questions. The researchers then began a two-month experiment. During the experimental period, the researcher, who was the instructor of the subjects, taught word meaning deriving strategies to students. The post-test, which was exactly the same as the pre-test, was given at the end of the experimental period. The results show significant differences of students correct guessing rates and the strategy choice between the pre-test and the post-test. This suggests that it is worthwhile teaching EFL students word meaning deriving strategies.